Measuring Mechanisms of Student Voice: Development and Validation of Student Leadership Capacity Building Scales - Lindsay Lyons; Marc Brasof; Carol Baron (SAGE Publishing, 2020)
This study developed measurement scales on student leadership capacity building through a survey of 280 students from nine U.S. high schools. Exploratory and confirmatory factor analyses resulted in a personal, interpersonal, organizational, and overall scale for building student leadership capacity. The scales included eight mechanisms that schools can use to enhance student leadership: pedagogy, relationships, radical collegiality, governance structure, research, group makeup, consistency, and recognition. The scale items also reflected three leadership competencies: critical awareness, inclusivity, and positivity. Focus groups and interviews with students and teachers in these nine schools supported survey findings and suggested implications for practice.